1993
DOI: 10.1159/000139840
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effects of Sennoside on Contractile Activity and Fluid Flow in the Perfused Large Intestine of the Rat

Abstract: The effect of sodium rhein on contractile activity and fluid flow in the rat complete large intestine was studied in vitro. Contractile activity was recorded using serosal strain gauges and volume transducers recorded distal fluid flow from the segment. Luminal sodium rhein (1 mM) produced a protracted increase in caecal activity yet increased colonic contractility transiently. Fluid flow from the preparation was increased and the number of propagated complexes was elevated after the initial 10 min of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It is also well known that rhein, an active metabolic product derived from microbial fermentation of the natural occurring sennosides, induces motor changes in the colon resulting in a faster passage of faeces (Capasso & Gaginella, 1997). However, only recently it has been demonstrated in vitro that sennosides derivatives increase circular muscle contractility (Rumsey et al , 1993) and peristalsis (Nijs et al , 1993), but it is not clear if this effect is due to a direct action on circular muscle, to activation of circular muscle motorneurons or to a multisynaptic pathways involving nicotinic synapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well known that rhein, an active metabolic product derived from microbial fermentation of the natural occurring sennosides, induces motor changes in the colon resulting in a faster passage of faeces (Capasso & Gaginella, 1997). However, only recently it has been demonstrated in vitro that sennosides derivatives increase circular muscle contractility (Rumsey et al , 1993) and peristalsis (Nijs et al , 1993), but it is not clear if this effect is due to a direct action on circular muscle, to activation of circular muscle motorneurons or to a multisynaptic pathways involving nicotinic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the difficulty to reproduce in vitro their stimulating effect on intestinal motility observed in vivo (Leng‐Peschlow, 1992). Indeed previous studies in vitro have documented that rhein decreases intestinal contractility in the rat intestine (Odenthal & Ziegler, 1988), but recently it has been shown that increased intestinal peristalsis in the guinea‐pig ileum (Nijs et al , 1993) and increased circular smooth muscle contractility in the rat intestine is produced by sennoside aglycones (Rumsey et al , 1993). However, it is still not clear whether sennosides derivatives act on smooth muscle, nerves or via activation of intrinsic reflexes.…”
Section: Introductionmentioning
confidence: 99%
“…Electromyo graphic measurements in rat colon in vivo revealed a decreased motility index after a high dose senna preparation within 2-4 h and total recovery was not observed within 20 h [4], In dogs fitted with strain gauge transduc ers, sennosides inhibited colonic motility in general, but sometimes giant contractions ap peared and were often associated with defaeca- tion [14]. In man, propulsive activity was the main feature observed after sennosides [6], Other experiments in the isolated, vascularly perfused complete large intestine of the rat showed a transient increase in colonic excitability and propulsive activity only after a very high concentration of rhein adminis tered luminally [15]. In the guinea pig ileum preparation a peristaltic reflex with an in crease in longitudinal muscle tension, intralu minal pressure and volume displacement was induced by mucosally applied rheinanthrone, another active metabolite of sennosides [16], Our method does not allow recognition of propagation of contractions but measures lo cal contractions of small colon segments.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal rhubarb herbs contain anthraquinones, dianthrones and glycosides (Kashiwada et al ., ; Lin et al ., ). These constituents contribute to various bioactivities such as purgative effects (Rumsey et al ., ; Kobayashi et al ., ), choleretic action (Chen et al ., ), liver‐protection effects and neuro‐protective effects (Chen et al ., ; Wang et al ., ; Dong and Zhang, ). Reports on rhubarb constituents also show the following activities: anti‐viral (Jing et al ., ; Li et al ., ; Chen et al ., ), anti‐inflammatory (Chang et al ., ) and anti‐carcinogenic (Jing et al ., ; Kang et al ., ; Xia et al ., ).…”
Section: Introductionmentioning
confidence: 98%